The Effect of Competence and Job Placement Fit on Employee Performance, with Motivation as a Mediating Variable Among Employees of The Secretariat General, Ministry Of Villages - Ambarwati, Tri; Herawati, Aty (Jurnal Ilmiah Sumber Daya Manusia, 2026)
Indonesia's Golden Vision 2045 transformation is hindered by low Civil Service Apparatus performance quality, where 35 percent of civil servants perform poorly and only 19.82 percent work optimally. Employee Performance Target data at the Ministry of Villages and Disadvantaged Regions shows fluctuation in "Good" category from 93.17% (2022) to 68.46% (2023) and 70.60% (2024), reflecting performance development inconsistency. This study aims to analyze the influence of competence and work placement suitability on employee performance through motivation as a mediating variable at the Secretariat General of the Ministry of Villages and Disadvantaged Regions. The research employs a quantitative causal-associative approach with 120 civil servant respondents through convenience sampling and PLS-SEM analysis using SmartPLS 3.3. Results indicate competence significantly influences work motivation (β=0.287; p=0.001) and employee performance (β=0.211; p=0.015), work placement significantly influences work motivation (β=0.500; p=0.000) and employee performance (β=0.295; p=0.005), work motivation significantly influences employee performance (β=0.418; p=0.000). Motivation mediates the influence of competence (β=0.120; p=0.005) and work placement (β=0.209; p=0.001) on performance with model predictive capacity R²=0.623 and Q²=0.803. The study recommends implementing continuous competency development programs, periodic evaluation of work placement suitability based on education and expertise, improving proportional compensation systems according to workload, and developing objective and transparent performance appraisal systems to support bureaucratic reform and merit system implementation.